Nutritional status and the behavior related to the elderhood of children who lives with elderly people (Research, Society and Development, 2022)
The objective of this study was to analyze the association between nutritional status and the attitudes of children living with the elderly in relation to old age. This is a cross-sectional study carried out with 141 schoolchildren aged 5 to 10 years. The children's attitude towards old age was evaluated and qualified through the application of the “Scale of Attitudes towards Old Age for Children”. Anthropometric data were measured according to the techniques standardized by the Food and Nutrition Surveillance System and the Brazilian Society of Pediatrics. The average score obtained by applying the Todaro Scale was 1.54 (± 0.45) points. There was a significant correlation between the average total score of the Todaro Scale and the Body Mass Index / Age of the children (p = 0.015), Waist Circumference (p = 0.032) and Waist and Height Ratio (p = 0.031) and between the domain cognition, Body Mass Index / Age (p = 0.031) and the Waist and Height Ratio (p = 0.047). The evaluated children who presented variables considered above the recommended ones showed positive attitudes towards old age, which indicates that there is a relationship between the nutritional status and the referred attitudes of the children.